Michelle Whitney: capstone - Whitney, Michelle, artist (Colorado State University. Libraries, 2025)
The artist's statement: Kapamilya is a Tagalog word that translates to "family member", however it is often used to describe a group of people who have a strong bond between them, regardless of being truly related by blood. These bonds may form and blossom from unexpected places. Someone who was once a stranger to your family could become a friend, a caretaker, a sibling, or some combination of the three which could only then be described as "family." I grew up in the Philippines, where most if not all of our meals at home were had together as kapamilya. Meals are a place to have conversations with one another about life. Meals hold space for you and your loved ones to share experiences, relate to one another, and strengthen bonds. This body of work takes inspirations from my experiences growing up in Northern Luzon as well as from research done on the Kalinga peoples of Northern Luzon and their making of traditional cooking vessels called Palayok. The making of these vessels pre-dates the long history of colonization which the Philippines went through. Despite colonization and colonial influences, palayoks are still made today through the same methods utilized and passed down from Filipino ancestors. Palayoks are hand-built, decorated with stamped motifs inspired by agricultural life, pit fired, and sealed with resin. The making of these pots was a labor born out of necessity for survival and love for family and community. Personally, this body of work is a labor born out of love for my culture, family, and friends. Though my work strays from traditional practices, I aim to create forms which celebrate the beauty of my culture and the coming together of people.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery